Bone and joint infection complicated with sepsis in neonates and infants under three months of age - Yao Liu; Kai Zhao; Ya Liu; Yu-Han Sun; Meng-Xia Li; Min Yu; Lun-Qing Zhu; Xiao-Dong Wang (Elsevier, 2024)
Objective: Studies focusing on bone and joint infections (BJIs) in young infants are rare. Some cases of BJI are accompanied by sepsis. This study aimed to identify the clinical and bacteriological features of sepsis in neonates and young infants with BJIs. Methods: Neonates and infants younger than 3 months diagnosed with BJI in the present institution from 2014 to 2021 were retrospectively reviewed. Patient characteristics, clinical data, and outcomes were documented and compared between those with and without sepsis. Results: Twenty-five patients with a mean age of 34.8 days were included. Nine BJI cases had concomitant sepsis (group A), and 16 had BJI without sepsis (group B). Within group A, staphylococcus aureus was the major pathogenic germ (5 cases, of which 4 were of the methicillin-resistant staphylococcus aureus (MRSA) type). There was no statistical difference in male-to-female ratio, age, history of hospitalization, anemia, birth asphyxia, peripheral leukocyte counts, C-reactive protein on admission, and sequelae between groups. Univariate analyses indicated a significant difference in the incidence of septic arthritis (SA) combined with osteomyelitis (OM) (88.9% vs 37.5%), congenital deformities (44.4% vs 0%), and mean duration of symptoms (2.83 days vs 9.21 days) in comparisons between groups A and B. Conclusion: Staphylococcus aureus is the main pathogenic bacteria in BJI cases complicated with sepsis in neonates and young infants. Among infants younger than 3 months diagnosed with BJI, those with concurrent SA and OM, MRSA infection, or congenital deformities are more likely to develop sepsis.